Dead ringers recalling obsolete machines in living rooms - Wrench, Melissa (Michaelis School of Fine Art, 2025)
My MFA project involves collecting, deconstructing and reimagining obsolete media machines to blur the lines between functional objects and visual spectacles. Tinkering techniques are employed as an art method to reanimate discarded electronics. Discarded electronic components are salvaged and repurposed, ultimately resulting in hybridised machines. The production evokes Mary Shelley's gothic novel, Frankenstein, or The Modern Prometheus (1818). The research draws on cautionary tales of mechanisation and interpretations of monsters as cultural disruptors; thus the project positions rearticulated obsolete machines as agents of resistance against systemised obsolescence. Their disruption conjures spectres, bringing forth unresolved histories. In addition, the artistic production resolves to validate Do-It-Yourself (DIY), hardware hacking and circuit bending techniques as speculative knowledge production. The findings manifest in a sculptural installation comprising altered telephones and fragmented furniture in a domestic space that has been made to seem strange. The installation questions the interplay between humans and machines, offering an interpretation of the cultural significance of technologies which endure despite their obsolescence.